Water absorption behaviour and its effect on the mechanical properties of hybrid interwoven cellulosic fibre composites - Maslinda, Abu Bakar @ Yahaya (Universiti Malaysia Perlis (UniMAP), 2017)
Master of Science in Mechanical Engineering